HOTPO as multidimensional performance: the performer as a sound based composition method - Portovedo, Henrique (2023)
The intertwining of computation with artistic environments leads to a state of permanent articulation and supports the development of artistic creation. Musical expressions are now based on two principles: the integration of tradition and technological means; and the rupture of all the contexts that cannot be seen as directly deriving from the computer and digital technology. HOTPO was developed over the specialised algorithmic composition software named Slippery Chicken developed by Michael Edwards, written in and functions on the principles of the Common Lisp Object System (CLOS), the Common Lisp facility for object- oriented programming. HOTPO is based on a reference to the Collatz Conjecture, a mathematical proposition that refers to a succession of numbers called the hailstone sequence (or wondrous numbers), because their values usually ascend and descend like hailstones in a cloud. The algorithm used generates section lengths and repeated structures from nine basic rhythm sequences, hence the composer’s sequence was 9 28 14 7 22 11 34 17 52 26 13 40 20 10 5 16 8 4 2 1. This piece explores microtonal relations of tone pitches and layers of multiphonics permutations. he multiphonics were organised into layers of tremolos, producing timbral changes and being selected thru a process that uses two different methods and softwares developed by Henrique Portovedo. The first method was implemented, SaxMultis, allows the recording of all multiphonic timbral permutations and its cataloging; this gives, as well, the possibility of generating aleatoric positions of key combinations.The second method, Multi2Chord, analyses the spectrum of each multiphonic permutation and translate it into musical notation. Understanding how emerging digital musical technologies trace their concepts, design and functionality to practices in the current cultural epoch will bring to light a study of new-media archeology, conceptual epistles and performative paradigms, directed, in other words, to the study of how the new technologies of mixed music-making trace their design to the practices of material, symbolic, signal inscription and how practice is transforming and leading to creation.